Desenvolvimento e caracterização de nanocápsulas de poli (L-lactídeo) contendo benzocaína - Melo, Nathalie Ferreira Silva de [UNESP]; Grillo, Renato [UNESP]; Rosa, André Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Dias Filho, Newton Luiz [UNESP]; Paula, Eneida de; Araújo, Daniele Ribeiro de (Sociedade Brasileira de Química, 2010)
In this paper we describe the preparation poly (L-lactide) (PLA) nanocapsules as a drug delivery system for the local anesthetic benzocaine. The characterization and in vitro release properties of the system were investigated. The characterization results showed a polydispersity index of 0.14, an average diameter of 190.1± 3 nm, zeta potential of -38.5 mV and an entrapment efficiency of 73%. The release profile of Benzocaine loaded in PLA nanocapsules showed a significant different behavior than that of the pure anesthetic in solution. This study is important to characterize a drug release system using benzocaine for application in pain treatment.
Development and characterization of poli (L-lactide) nanocapsules containing benzocaine
Keywords: local anesthesic; PLA nanocapsules; drug release